Outplacement and continuity in employment - López-Mena, Luis (Revista de Psicología, 1997)
In this work we revised the historical development of Outplacement technology by applied psychology to industry. Psychologists used models of work, concepts, and general strategies in counselling-training to access employment market and research about influences psychological factors to obtain employment; for example: self-esteem was found to predict a) the sources individual used to find jobs; b) interview evaluactions received from organizational recruiters, c) satisfaction with job search; d) number of offers received; e) acceptance of a job before graduation; f) lenght of intended tenure. Global self-steem proved a better predictor of search outcomes dependent on participant’s social skills, whereas task-specific self esteem was more strongly related to search motivation and satisfaction. Bandura’s theory of self-efficacy indicates that individuals of low general self-efficacy should be given priority access to scarce behavioral-modeling training resources. We present a scheme of program for obtained employment in Chile, and the benefit-cost analysis of the job-finding programs.